2014
DOI: 10.1186/1471-2458-14-s3-s6
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on risk factors for chronic non-communicable diseases among adolescents in Malaysia: overview of the Malaysian Health and Adolescents Longitudinal Research Team study (The MyHeART study)

Abstract: Background: The National Health & Morbidity Survey (NHMS) IV (2011) observed that the prevalence of obese children aged less than 18 years in Malaysia is 6.1% compared to 5.4% overweight and obese in NHMS III (2006). As such, this observation is of public health importance as obesity is a forewarning risk factor for chronic diseases such as type-2 diabetes, cardiovascular diseases (CVD) and certain types of cancers. This MyHeART (Malaysian Health and Adolescents longitudinal Research Team) study aims to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 26 publications
2
56
1
Order By: Relevance
“…In fact, it was in accordance with the Hazreen et al finding in Malaysia (20). Some studies on Turkish (21) and Brazilian (22) adolescents have respectively reported hypertension prevalence as 4.4% and 21.3%.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In fact, it was in accordance with the Hazreen et al finding in Malaysia (20). Some studies on Turkish (21) and Brazilian (22) adolescents have respectively reported hypertension prevalence as 4.4% and 21.3%.…”
Section: Discussionsupporting
confidence: 78%
“…The present study revealed that hypertension in boys was significantly more; however, previous studies had reported various results (7,(20)(21)(22). More prevalence of hypertension during teenage may be due to anxiety, stress, and also hormonal changes resulting from puberty.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The subjects were adolescents from government schools, with the exception of boarding, religious, and vernacular schools. The study protocol was published [28] and approved by the Medical Ethics Committee, University Malaya Medical Centre (MEC Ref. No.…”
Section: Methodsmentioning
confidence: 99%
“…In Malaysia, the 4 th National Health and Morbidity Survey 2011 reported a 6.1% prevalence of obesity among Malaysian children under 18 years of age, with higher rates occurring in urban areas7. A recent longitudinal cohort study involving 1,361 Malaysian adolescents had documented a 9% prevalence of obesity8, suggesting a continuous increase in the childhood obesity prevalence rate. These increasing trends are alarming, as childhood obesity is closely associated with increased risk of obesity and cardio-metabolic diseases in adulthood9.…”
mentioning
confidence: 99%